Analysis of Argo Parahyangan Train Passenger Interest to Jakarta-Bandung High-Speed Train - Aang Gunawan; Hendar Kusnandar; Abdullah Ade Suryobuwono; Lia Fauziah Nadira; Siti Nurhidayah (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The Argo Parahyangan train is one of the services provided by PT.KAI (Persero) with Jakarta-Bandung relation is much in demand by the public. The newly commencement Jakarta-Bandung High-Speed Train, with a short time of 36-44 minutes, a maximum capacity of 601 passengers, and a ticket price similar to the Argo Parahyangan train make new competition with the Argo Parahyangan train. This study aims to determine the characteristics and factors influencing modal shifts and calculate the probability of switching Argo Parahyangan train passengers to the Jakarta-Bandung High-Speed Train. The research method used is quantitative. The data collection method used in this research is conducting an online interview survey using revealed preference and stated preference techniques. The total sample in this study was 165 respondents on the results of the slSlovinormula calculation of total Argo Parahyangan Train Passengers in one week mode shift analysis using the binomial logit analysis.